Radio emissions of auroral origin observable at ground level: outstanding problems - LaBelle, James (Frontiers in Astronomy and Space Sciences, 2023)
Auroral radio emissions are of intrinsic interest as part of the Earth's environment but also provide remote sensing of ionospheric conditions and processes and a laboratory for emission processes applicable to a wide range of space and astrophysical plasmas. At VLF and above, four broad classes of radio emissions occur. All have been observed with ground-based and, in some cases to a lesser degree, with space-based instruments. Related to each type of radio emission, many experimental and theoretical challenges remain, for example: explanations of frequency and time structure, relations to auroral substorms or current systems, and application to remote sensing of the auroral ionosphere. In some cases, basic parameters such as source heights or generation mechanisms are uncertain. Emerging technological advances such as cubesat fleets, ultra-large capacity disk drives, and software defined radio show promise for developing better understanding of auroral radio emissions.